Fermentation parameters in the rumen of goats supplemented with polyphenol oxidase derived from Gliricidia sepium leaves under in vitro conditions - ASRI NURUL HUDA; AKHMAD SABARUDIN; ANURAGA JAYANEGARA; HENDRAWAN SOETANTO (Society for Indonesian Biodiversity, 2023)
Abstract. Huda AN, Sabarudin A, Jayanegara A, Soetanto H. 2023. Fermentation parameters in the rumen of goats supplemented with polyphenol oxidase derived from Gliricidia sepium leaves under in vitro conditions. Biodiversitas 24: 3282-3290. The growing demand for healthy foods derived from ruminant products is restricted by the high content of saturated fatty acids in meat or milk due to the process of rumen biohydrogenation. Recent reports from intensive studies using polyphenol oxidase (PPO), an enzyme in plants’ secondary metabolism, as the inhibitor of rumen biohydrogenation cost doubt of ruminant products. PPO is assumed to increase the supply of UFA by reducing the rate of biohydrogenation due to rumen microbes’ activity. Microbes of the rumen, including species of bacteria and protozoa are responsible for rumen biohydrogenation. The present study investigated the effect of adding PPO derived from Gliricidia sepium leaves on fermentation parameters in the rumen, including protozoa density and diversity, fatty acid profile, volatile fatty acid profile, and the efficiency of microbial protein synthesis under in vitro conditions. The experiment was carried out through an in vitro rumen fermentation method, consisting of five treatments, i.e., negative control, positive control, the addition of 0.1 ml, 0.3 ml, and 0.5 ml PPO emulsion. The most dominant type of protozoa among all treatments was Entodinium spp. PPO emulsion increases the efficiency of microbial protein synthesis and volatile fatty acid concentration. 0.5 ml PPO emulsion increases linoleic acid. In conclusion, this finding poses a question on the role of rumen protozoa in lipid biohydrogenation in the rumen. A further experiment on the benefits of adding PPO regarding rumen biohydrogenation under in vivo conditions is warranted.